Acoustic evaluation of leisure events in two mediterranean cities. (March 2015) - Ballesteros, Mª Jesús; Fernández, Marcos D.; Ballesteros, José A.
Highlights: The noisiest group of events are the popular festivities. The least nosy events are the Easter processions except 'Turbas'. According to this study, events in small cities are noisier than big cities. People complain more about new festivities or those not destined to all people. The measurement procedure allows simulating the events in different places. Abstract: Nowadays, leisure noise is one of the most important noise pollutants. It is thought that this kind of noise is only present outside bars and discotheques. However, this is not true, especially in Mediterranean cities, because noise is also found in concerts, popular festivities, sport events or religious celebrations. These occasions produce high noise levels; and depending on the kind of event, these are repeated with more or less frequency. Besides, in some cases, they take place at night, so the annoyance is higher for more people. For this reason, people who complain about these circumstances increase every year. This paper is about this kind of noise in two Mediterranean cities with very different characteristics. In both of them, the most important leisure events that take place along a year have been measured. Binaural measurements have been taken to characterize them from the acoustic point of view and to evaluate the acoustic pollution. Moreover, the potential number of affected residents has been calculated in order to estimate how many people could suffer any annoyance because of this kind of noise. Finally, a comparison of the sound level measured and the potential number of disturbed residents in each leisure event in both cities has been carried out, considering the type of city as another variable in the noise produced by the mentioned leisure events.